ANALISIS KETERAMPILAN MENGUKUR SISWA SEKOLAH DASAR - Annisa Qomariah Nisa (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2023)
This study aims to determine the implementation of science process skills on temperature and heat material through the aspect of measuring skills in learning by students at SDN 015 Samarinda Ulu. The sampling technique used was purposive sampling, the subjects of this study were home teachers of class V, students of grade V, and parents of students of grade V. The data collection techniques used were interviews and documentation and then the data were analyzed using data collection techniques, data reduction, data presentation, and conclusion. The type of triangulation used is source triangulation. Teachers and parents have made efforts so that students always work on assignments regarding measurement, among others, by always reminding students about the assignments that have been given by the teacher, parents will also encourage students to carry out assignments or do assignments. As for the stages of implementing learning regarding measurement, namely the homeroom teacher will provide a brief explanation regarding the implementation process of learning about measurement and practicum media that will be used so that students can immediately carry out practicum at home with the assistance of their parents, and to see the results of practicum students the teacher gives assignments to students related to practical results. Keywords: Science Process Skills, Basic Skills, Measuring Skills.